Out Of Sync: The Emotional and Social Cost Of Living Ahead Or Behind One’s Time - Amirsheibani, Morteza; Yo'ldoshev Abdug'aniyevich , Otabek (CV. Doki Course and Training, 2025)
This study deals with the emotional and social outcomes brought upon individuals who consider themselves as temporally misaligned either behind or ahead of the prevalent cultural and ideological standards at that time. Based on the cultural lag theory (Ogburn, 1922) and existential psychology (Yalom, 1980), this study examines the influence of temporal dissonance on identity, belonging, and well-being. The paper adopted a phenomenological research design in the form of in-depth semi-structured interviews with sixteen respondents, divided into two groups: those who consider themselves traditionalists and are finding it challenging to adjust to the changes of modern times, and those who consider themselves visionaries and are getting upset about the pace of social change. A thematic analysis unveiled these five major findings: temporal alienation, social misrecognition, emotional burden, tension in identity, and coping mechanisms wherein different belief systems led to identical underlying experiences of psychic pain and marginalization. Many also showed strengths by creating different value systems and support groups. These results suggest that time not being in line is a meaningful way of looking at who a person is and how they feel, and it should be studied more in the fields of culture and psychology.